PETROGENESIS AND TECTONIC SETTING OF CADOMIAN FELSIC IGNEOUS ROCKS, SANDıKLı AREA OF THE WESTERN TAURIDES, TURKEY - Gürsu S.; Göncüoglu M.C. (My University, 2006)
In the Sandıklı (Afyon) region, western Taurides, the Late Proterozoic rocks of the Sandıklı basement complex are composed of low-grade meta-sedimentary rocks (Güvercinoluk Formation) intruded by felsic rocks (Kestel Cayı Porphyroid Suite, KCPS). The KCPS is a deformed and highly sheared, dome-shaped rhyolitic body with a granitic core. Quartz porphyry dikes intrude both the slightly metamorphic igneous and the sedimentary rocks of the basement complex. Both the quartz porphyries and rhyolites were converted into mylonites with relict igneous textures. Geochemical data show that these felsic igneous rocks are subalkaline and mainly granitic in composition with SiO2 >72 wt% and Al2O3 >11.5 wt%. The chondrite-normalized incompatible trace element patterns are characterized by distinct negative Rb, Nb, Sr, P, Ti, and Eu with enrichment in Th, U, La, Ce, Nd, Sm, and Zr. The REE patterns of the felsic rocks indicate a strong enrichment in LREE but display slightly flat HREE patterns. According to geochemical characteristics and petrogenetic modeling, extrusive and intrusive rocks of the KCPS were probably derived from an upper continental crustal source (partial melting of granites/felsic rocks) by 18–20% fractional melting plus 18–20% Rayleigh fractional crystallization, which seems to be the most effective igneous process during the crystallization of the KCPS. Single zircon age data from the granitoids and fossils from the disconformably overlying sedimentary successions indicate that the metamorphism and the igneous event in the Taurides are related to the Cadomian orogeny. Based on the geological, geochemical and petrogenetic correlation of the post-collisional granitoids it is further suggested that the Tauride belt in western central Turkey was in a similar tectonic setting to the Gondwanan terranes in North Africa (Younger Granitoids) and southern Europe (Spain, France, Bohemia, Brno Massifs) during the Late Cadomian period.
Keywords: I-TYPE GRANITES; RHYOLITES/QUARTZ PORPHYRY ROCKS; POST-COLLISIONAL; TAURIDES; LATE PAN-AFRICAN; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой